The Development of Authentic Assessment Instrument to Measure Science Process Skill and Achievement based on Students' Performance - Atin Kurniawati; Sukardiyono Sukardiyono (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2018)
This study aims to develop an authentic assessment instrument based on students' performance. It can build the science process skill and measure the cognitive aspects of student’s achievement. The procedure of research & development method is adapted from Borg and Gall’s model, consisting collecting information, planning, early product development, preliminary field testing, first product revision, field testing, second product revision, and dissemination. The initial field testing was executed to 15 participants, and the field testing to 31 participants in MAN III Yogyakarta use the One – Shot Case Study model. The results of the study as follows: (1) instruments according to the experts' judgment, physics teachers and peers, in general, was valid, (2) instruments at the preliminary field test and main field test was reliable, and (3) instruments could build skills and measure cognitive achievement’s aspect of the scientific process skills of the senior high-school students for heat and temperature topic.